Metronidazole Immediate Release Formulations: A Fasting Randomized Open-Label Crossover Bioequivalence Study in Healthy Volunteers - de Freitas Silva, M.; Schramm, S. G.; Kano, E. K.; Koono, E.E. M.; Manfio, J. L.; Porta, V.; dos Reis Serra, C. H. (Arzneimittelforschung, 2012)
Metronidazole is a BCS (Biopharmaceutics Classification System) class 1 drug, traditionally considered the choice drug in the infections treatment caused by protozoa and anaerobic microorganisms. This study aimed to evaluate bioequivalence between 2 different marketed 250 mg metronidazole immediate release tablets. A randomized, open-label, 2×2 crossover study was performed in healthy Brazilian volunteers under fasting conditions with a 7-day washout period. The formulations were administered as single oral dose and blood was sampled over 48 h. Metronidazole plasma concentrations were determined by a liquid chromatography mass spectrometry (LC-MS/MS) method. The plasma concentration vs. time profile was generated for each volunteer and the pharmacokinetic parameters Cmax, Tmax, AUC0–t, AUC0–∞, ke, and t1/2 were calculated using a noncompartmental model. Bioequivalence between pharmaceutical formulations was determined by calculating 90% CIs (Confidence Intervall) for the ratios of Cmax, AUC0–t, and AUC0–∞ values for test and reference using log-transformed data. 22 healthy volunteers (11 men, 11 women; mean (SD) age, 28 (6.5) years [range, 21–45 years]; mean (SD) weight, 66 (9.3) kg [range, 51–81 kg]; mean (SD) height, 169 (6.5) cm [range, 156–186 cm]) were enrolled in and completed the study. The 90% CIs for Cmax (0.92–1.06), AUC0–t (0.97–1.02), and AUC0–∞ (0.97–1.03) values for the test and reference products fitted in the interval of 0.80–1.25 proposed by most regulatory agencies, including the Brazilian agency ANVISA. No clinically significant adverse effects were reported. After pharmacokinetics analysis, it concluded that test 250 mg metronidazole formulation is bioequivalent to the reference product according to the Brazilian agency requirements.
Keywords: metronidazole; human plasma; bioequivalence; biowaiver; HPLC-MS/MS